Perspectives of endodontic treatment of deciduous teeth using the CTZ antibiotic paste: a integrative review (Research, Society and Development, 2022)
Introduction: The main function of endodontic treatment in primary teeth is to obtain a correct conformation of the root canals, enabling an adequate disinfection, in order to avoid possible extractions, as it is also used to preserve masticatory, aesthetic and phonetic functions, which are still under development. Antibiotic-containing pastes have shown great clinical relevance and a high success rate. Objective: Evaluate the available scientific evidence on the use of anti-biotic toothpaste CTZ as filling material for primary teeth in order to draw attention to the risks and benefits of using this medication. Material and methods: Search strategies were developed for the following databases: PubMed, Scielo, Cochrane and Lilacs. The guiding question of the research was: What are the main clinical indications for the use of CTZ antibiotic paste in the endodontic treatment of deciduous teeth and what are the advantages and disadvantages of using this technique? Results: The results demonstrated significantly higher concentrations of better clinical results in techniques that made use of pulpotomy with the CTZ paste for the treatment of severe caries. Regarding the clinical success of the included clinical studies, about 66.7% had complete clinical success, with no postoperative changes. Regarding radiographic success, 55.7% of the studies had total radiographic success, and only 33.3% had a result below 95%. Conclusion: Despite the known clinical success of the endodontic technique, there is a need to develop studies in order to verify the clinical and radiographic results of treated primary teeth. Also, verify the influence of the treatment on the development of permanent successor teeth.